Degradation of High Concentrations of Anthracene Using White-Rot Wood-Inhabiting Fungi and Investigation of Enzyme Activities - Mohadeseh Khajehzadeh; Masoomeh Ghobad-Nejhad; Hamid Moghimi; Ali Abolhasani Soorki; Yu-Cheng Dai; Jing Si (Mycobiology)
Owing to the production of lignin-modifying enzymes (LMEs), white-rot fungi (WRF) such as polypores are potent organisms in the biodegradation of xenobiotic pollutants. The nonspecific function of LMEs including laccase and manganese peroxidase (MnP), has enabled the use of WRF in biotechnological applications, particularly in bioremediation. In this study, 12 strains from nine white-rot basidiomycete genera viz., Ganoderma, Inocutis, Irpex, Lentinus, Lenzites, Oxyporus, Peniophora, Sanghuangporus, and Trametes were isolated from Iran and identified using morphological and molecular tools. The enzyme activity of laccase and manganese peroxidase that directly correlated with the biodegradation were determined, and the strains with the highest enzyme activities were evaluated for their ability to degrade 400 mg/L of anthracene over 28 days. Gas chromatography with flame ionization detector (GC-FID) revealed that four polypores viz., Trametes versicolor v21te, T. versicolor v22da, T. hirsuta, and Oxyporus sp. degraded 64%, 52%, 34%, and 20% of the anthracene, respectively. According to our analysis, the examined indigenous WRF are potentially useful candidates for the development of new mycoremediation techniques to degrade polycyclic aromatic hydrocarbons (PAHs).